Effects of 2,4,6-trihydroxy-3-geranyl acetophenone on growth factor-induced human bronchial smooth muscle cell proliferation in asthma - Yap, Hui Min (2018)
Asthma is a chronic inflammatory disease of the airways, which can be characterized by airway remodeling and hyperresponsiveness. Increased airway smooth muscle (ASM) mass appears to be a prominent hallmark of airway remodeling attributed to the release of mitogenic factors during the inflammatory process. Corticosteroids and beta-agonists remain the mainstay of current asthma treatment, but do not specifically target airway remodeling. Previous studies have shown that 2,4,6-trihydroxy-3-geranyl acetophenone (tHGA), a non-steroidal synthetic compound, demonstrated anti-inflammatory activity as well as anti-remodeling properties in a chronic murine model of asthma. In this study, the effects of tHGA upon human bronchial smooth muscle cell (hBSMCs) proliferation, apoptosis and migration in response to growth factors was evaluated. hBSMCs were serum-starved overnight prior to induction with growth factor-enriched medium and co- treated with tHGA or forskolin for 48 hours. Cell cycle analysis was carried out to examine the mechanism of action of tHGA upon hBSMCs proliferation. Expression of cell cycle proteins cyclin D1 and p27Kⁱᵖ¹ was assessed through immunoblotting. The identification of the molecular target of tHGA involved expression studies upon major proliferation-associated signaling pathways involved in ASM proliferation, which include MAPK, PI3K and JAK2/STAT3. Signaling pathways were examined through immunoblotting, immunoprecipitation and kinase assays while the potential molecular target was reconfirmed through transfection. tHGA, at concentration of 20 µM and below, did not cause significant release of LDH, thus was used in the following experiments. tHGA, at concentration of 20 µM and 10 µM, was shown to significantly inhibit hBSMCs proliferation and migration without inducing apoptosis. tHGA, at 20 µM, reduced hBSMCs proliferation to 46.9 ± 5.2% as compared to growth factor-induced cells (100%). This finding was further reconfirmed through Ki-67 expression study. tHGA, at 20 µM, inhibited Ki-67 expression in growth factor-induced cells from a fold change of 1.03 ± 0.03 to 0.43 ± 0.11. The anti-proliferative effect was due to cell cycle arrest at the G1 phase accompanied by a reduction of cyclin D1 and diminished degradation of p27Kⁱᵖ¹ expression. tHGA, at concentration of 20 µM and 10 µM, significantly increased the percentage of hBSMCs at G1 phase from 39.7 ± 2.1% to 71.6 ± 2.0% and 50.6 ± 1.3% respectively. Besides that, scratch assay revealed that 20 µM of tHGA attenuated cell number of hBSMCs that migrated to the scratch area from 108.6 ± 7.5 cells/mm² to 36.2 ± 11.0 cells/mm². Analysis of proliferation-related signaling pathways demonstrated tHGA to act as an inhibitor of AKT, JNK and STAT3 phosphorylation. tHGA did not affect the activation of the upstream activators of STAT3 and AKT, thus the potential molecular target was narrowed down to AKT. The major effect upon phosphorylation of AKT was further confirmed following treatment of hBSMCs transfected with constitutively-active AKT (myr-AKT). tHGA was suggested to inhibit the phosphorylation of AKT that leads to cyclin D1 downregulation and growth inhibition. This study highlights the anti-remodeling potential of this drug lead in chronic airway disease.